Investigating Gamma-Ray Bursts and Their Potential as Standard Candles Through the Optical Luminosity-Time Correlation - Livermore, Samantha M. (Tufts Archival Research Center, 2022)
Gamma-ray bursts (GRBs) are incredibly luminous events that can be observed out to the very early Universe. Recent decades have brought improved time-resolution, rapid-response detection, and expanded observation capabilities in multiple electromagnetic bands, which have enabled the investigation of multi-wavelength GRB afterglows and allowed for the determination of GRB redshifts. In order to fundamentally understand GRBs and to use them to study the early Universe, it is critical to study their characteristicsand light curve behaviors. In this work, we discuss the standard models of GRB progenitors and emission mechanisms, their potential as possible standard candles, and some background on past GRB parameter correlations. We investigate the plateau emission feature in optical GRB light curves for a large sample of Swift GRBs with known redshifts and gather the largest set of optical plateaus to date (102). Building off of the work done in Dainotti et al. (2008) and Dainotti et al. (2013) on X-ray plateaus and the X-ray luminosity-time correlation, we investigate the optical luminosity-time correlation between the time at the end of the plateau phase T ∗ opt and the luminosity at the end of the plateau Lopt(T ∗opt). We determine that the luminosity-time correlation exists in this large sample of optical plateaus and is comparable to the equivalent correlation in X-rays. We also find that the slope of the optical correlation is in agreement with the magnetar model describing the plateau emission. We compare a subset of our General Sample with both X-ray andoptical observations and find that the end-time of the plateau is achromatic between the two bands.; Thesis (B.S.)--Tufts University, 2021.; Submitted to the Dept. of Physics and Astronomy.